Analysis of critical failure factors in ERP implementation: an Indian experience. (1st January 2012) - Sar, Archana; Garg, Poonam
The opening of economy and changes in the economic policies during the early 90s opened up the market for Indian manufacturers. They become the global suppliers to large manufacturers across the globe. This change forced many manufacturers to adapt to the modern technologies like enterprise resource planning (ERP) to comply with the business requirement of the global manufacturers and to reduce time of delivery. Due to the lack of any crucial resources, 60% to 70% of the ERP projects are not implemented successfully. This study examines the current literature on causes of ERP implementation failure in context to Indian manufacturing sector. The study is then subjected to root-cause analysis of the failure factors to which the Pareto analysis is applied to identify the vital factors. The top two vital factors are sub divided into various factors and the top sub five factors are abstracted based on the frequency of occurrences of these factors in the literature.